Hue dual-chromatic calcium chlorosilicate phosphor for light-emitting diode having yellow and white illumination - Huu Phuc Dang; Bui Van Hien; Nguyen Le Thai (Institute of Advanced Engineering and Science, 2022)
High-thermal solid phase reactions produced a series of bright green-yellow phosphors called Ca3SiO4Cl2,Eu2+,Mn2+ (CaM). For example, powder dispersed reflection, photoluminescence excitation (PE), and along with emission spectra, were used to determine their luminous characteristics at between 10 K and 450 K of temperature. While the CaM exhibits wide absorption bands in the 250-450 nm range, which matches the near-uv of the InGaN-based chips, they also display two dominant absorptions, attributed to the 5d → 4f Eu2+ transformation, as well as the 4T1g(4G) → 6A1g(6S) transfer of the two ions Eu2+ and Mn2+, respectively. Increasing the concentration of Mn2+ ion reduces the lifespan of the Eu2+ ion. This encourages an efficient energy exchange between these two ions. The UV light leakage issue in yellow LEDs was resolved by intergrating with n-UV InGaN chips and CaM. Powerful white LEDs were then created by mixing blue chlorophosphate with CaM. Its color coordinate was (0.3281,0.3071), and the associated color temperature (TC) was 6065 K, while the general hue rendering (Ra) and illuminating effectiveness (11 lm/W) were respectively 84.5 and 11 lm/W.